Fulfillment of Constitutional Rights for Child Victims of Sexual Violence in Batang Regency - Rizkiyah, Ulva Syakirohtul; Kamalludin, Iqbal (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
In 2022, there were 16 children victims of child sexual violence in Batang Regency, while in 2023 the number of child victims of sexual violence reached 50 victims. The government is responsible for providing security and welfare for every child victim of sexual violence based on Article 28 B paragraph (2) of the 1945 Constitution of the Republic of Indonesia. This paper is empirical legal research using a qualitative approach. The results of the research found that the fulfillment of the constitutional rights of children victims of sexual violence in Batang Regency has not been implemented optimally, shown among other things by the lack of fulfillment of the rehabilitation rights that should be obtained by children victims of sexual violence, as well as the legal culture of the people of Batang Regency which is still low in protecting children victims of violence. sexual. Children who do not receive rehabilitation and children who are victims but whose cases are not reported have the potential to have personality disorders due to trauma and psychological shock.